The wedding - Sparks, Nicholas (New York : Vision, 2005)
A story of an ordinary man who goes to extraordinary lengths to win back the love of his life... After thirty years, Wilson Lewis is forced to face a painful truth: the romance has gone out of his marriage. His wife, Jane, has fallen out of love with him, and it is entirely his fault.
Keywords: Spouses -- Fiction; American fiction